Determination of Sambucus Interspecific Hybrid Structure using Molecular Markers - Šiško, Metka; Ivanuš, Anja; Ivančič, Anton (Agricultura Scientia, 2020)
Phenotypic and genotypic variations within the genus Sambucus are limited. They could be efficiently increased by genetic recombination involving different species. The aim of the presented investigation was to assess the possibility of using molecular approach (i.e., microsattelites) in determination of unknown hybrid structures. The study involved 47 Sambucus genotypes (parental species and intespecific hybrids), and six microsatellite loci were analysed. The clustering method grouped the analysed genotypes into four main groups. The first main group involved two sub-groups: one with taxons and hybrids involving S. racemosa (in broad sense) and the other involving two botanical varieties of S. nigra. In the second main group, there was a sub-group involving hybrids between S. javanica and S. nigra, and a sub-group involving F1 hybrids between S. javanica and S. ebulus. The third main group contained a sub-group with hybrids between S. javanica and S. nigra ‘Black Beauty’, a sub-group with hybrids involving S. javanica, S. nigra and S. racemosa (miquelii), a sub-group with backcrosses S. javanica × (S. javanica × S. ebulus), and un unknown hybrid. The fourth main group included a subgroup with F1 hybrids S. javanica × S. ebulus, a sub-group involving various taxons of S. racemosa (in broad sense), and a sub-group involving hybrids between S. cerulea and S. javanica, with and without S. nigra. Our study shows that molecular analysis can be helpful in determining some of the unknown but simple interspecific hybrids of Sambucus. In the cases of complex hybrid combinations, the use of SSRs is most probably not the best solution.
Keywords: Sambucus; SSR markers; interspecific hybrids; clustering method; molecular markers